2010
DOI: 10.1021/jp1002325
|View full text |Cite
|
Sign up to set email alerts
|

H+- and Al2+-Codoped Al2O3 Nanoparticles with Spinel-Type Related Structures by Pulsed Laser Ablation in Water

Abstract: Pulsed laser ablation in water under a high peak power density of 1.8 × 1011 W/cm2 using Q-switch mode and 1064 nm excitation was used to fabricate (H+,Al2+)-codoped Al2O3 nanocondensates having γ- and its derivative θ-type structure as characterized by electron microscopy and spectroscopy. The as-formed γ- and θ-Al2O3 nanocondensates are mainly 10 to 100 nm in size and have a significant internal compressive stress (>10 GPa) according to cell parameters and vibrational spectroscopy, due to a significant shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…This method offers some advantages such as rapid and high purity process compared with other methods [8]. Moreover, synthesizing NPs through laser ablation via liquid is simpler than the by gas atmosphere [9,10]. The present study attempted to prepare AlO 2 NPs by using liquid particles treated with laser technology (1064 nm) and energy (350 MJ), and to study their medical application as antibacterial and stimulation of wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…This method offers some advantages such as rapid and high purity process compared with other methods [8]. Moreover, synthesizing NPs through laser ablation via liquid is simpler than the by gas atmosphere [9,10]. The present study attempted to prepare AlO 2 NPs by using liquid particles treated with laser technology (1064 nm) and energy (350 MJ), and to study their medical application as antibacterial and stimulation of wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse lasers of short duration are also employed in the synthesis of nanoparticles of Al2O3. [30][31][32] In the relatively simple, Sol-gel methods, precursors such as aluminum triisopropylate 33 , aluminum nitrate 34,35 and aluminum secondary butoxide 36 are used. Parida et al(2009), synthesized γ-alumina using aluminum nitrate as precursor and found that the precipitation by NH4HCO3 resulted in spherical particles of4.7-5.7 nm size with 190 m 2 /g surface area and nearly 0.467 cm 3 /g pore volume.…”
Section: Introductionmentioning
confidence: 99%
“…Hz, 850 mJ) of an Al target in DI water [22] while ablation in aqueous solution of NaOH (0.05-1 M) lead to the fabrication of epitaxial β-NaAlO 2 and γ-Al 2 O 3 nanoparticles [23]. Hollow amorphous Al 2 O 3 micro/nanoparticles which may had weak crystallization were synthesized by pulsed KrF excimer laser ablation (30 ns, 248 nm, 10 Hz, 2.3 J/cm 2 ) of a bulk Al target in distilled water [24].…”
Section: Introductionmentioning
confidence: 99%